On Turkish Candidate Science Teachers’ Pre-existing Ideas About Some basic Astronomy Concepts - Kurnaz, Mehmet Altan; Gültekin, Nezihe Gökçen; İyibil, Ümmü Gülsüm (Elsevier BV, 2013)
AbstractDetermining pre-existing ideas is an important strategy to construct learning environment and improve learning. This study is designed to reveal Turkish candidate science teachers’ pre-existing ideas about some basic astronomy concepts. In fact, this study is a continuation of a study carried on pupils from different grades at secondary and high schools. In this regard, the study is remarkable to allow a comparison between perceptions of the candidate teachers and pupils. The participants of the study were 118 candidate science teachers from two universities. A data meaning-analysis table was used as the data collection tool. The gathered data was analyzed through classifying, which was shown in tables. The findings have showed that the candidate teachers did not have adequate knowledge to match the given astronomy concepts with their characteristics. In addition, the findings also indicated that consistency of candidate teachers’ responses to concepts and examples of these concepts were not sufficient. Based on the findings, some suggestions were made to curriculum developers, researchers and teachers.
Keywords: basic astronomy concepts; meaning-analysis table; candidate science teachers.; 4. Education